2021
DOI: 10.3390/ijms222212332
|View full text |Cite
|
Sign up to set email alerts
|

NTRK Gene Fusion Detection in Atypical Spitz Tumors

Abstract: Atypical Spitz tumors (AST) deviate from stereotypical Spitz nevi for one or more atypical features and are now regarded as an intermediate category of melanocytic tumors with uncertain malignant potential. Activating NTRK1/NTRK3 fusions elicit oncogenic events in Spitz lesions and are targetable with kinase inhibitors. However, their prevalence among ASTs and the optimal approach for their detection is yet to be determined. A series of 180 ASTs were screened with pan-TRK immunohistochemistry and the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…), but this is beyond the scope of this article [ 6 ]. Since these genetic alterations lead to an over- and/or aberrant expression of specific molecules, and the latter are associated with well-defined histological features of the melanocytic lesion, an expert dermatopathologist could suspect a specific genetic alteration from just the H&E exam and prove it with the immunohistochemistry [ 6 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. In our routine practice, we do not use standard panels; the choice of immunohistochemical panels is performed case-by-case, based on the H&E exam.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…), but this is beyond the scope of this article [ 6 ]. Since these genetic alterations lead to an over- and/or aberrant expression of specific molecules, and the latter are associated with well-defined histological features of the melanocytic lesion, an expert dermatopathologist could suspect a specific genetic alteration from just the H&E exam and prove it with the immunohistochemistry [ 6 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. In our routine practice, we do not use standard panels; the choice of immunohistochemical panels is performed case-by-case, based on the H&E exam.…”
Section: Diagnosismentioning
confidence: 99%
“…Specifically, the antibodies we use in our laboratory and specific histological entities, related to their over- and/or aberrant expression, are the following: -BRAF V600E: melanocytic lesions in intermittently sun-exposed skin (superficial spreading cM, simple lentigo, conventional and/or lentiginous cN, and dysplastic cN), deep-penetrating cN, BAP1 -inactivated melanocytic lesions, pigmented epithelioid melanocytoma (PEM), acral melanocytic lesions (especially cM), nodular cM (less frequent), and nevoid cM (less frequent); -c-Kit/CD117: acral melanocytic lesions (especially cM), and lentigo maligna; -ALK, ROS1, pan-TRK (NTRK1, NTRK2, and NTRK3), RET, and MET: Spitz lesions (also Reed cN) and acral melanocytic lesions (especially cM); -β-catenin: deep-penetrating cN, rare cases of cM with a “deep-penetrating like silhouette”; -PRKAR1A: PEM; -BAP-1: BAP1 -inactivated melanocytic lesions, cM arising in blue cN and atypical cellular blue tumor (rare cases); -NF1: lentigo maligna, desmoplastic cM, and acral melanocytic lesions (especially cM); -IDH1: recently introduced category of melanocytoma. In this diagnostic setting, although the immunohistochemistry has shown excellent concordance rates with molecular biology techniques (PCR, FISH, and NGS) and, therefore, represents a reliable, feasible, time- and money-saving tool for investigating these lesions, it is usually adopted as a “screening tool”, and the molecular biology techniques are adopted to confirm and expand the genetic background of the analyzed lesions [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. These techniques, differently from the immunohistochemistry, are able to identify the specific mutations and/or fusion partners; these data could provide relevant pathogenetic, prognostic, and therapeutic indications (specific mutations are associated with pharmacological resistances; additionally, specific fusions are associated with marked pharmacological sensitivity to kinase inhibitors) [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In more recent years, genomic studies have shown that most Spitz neoplasms harbor serine–threonine kinase mutations (HRAS, or more rarely MAP2K1) or receptor tyrosine and serine–threonine kinase fusions (ALK, ROS1, NTRK1, NTRK3, MAP3K8, more rarely BRAF, RET, MET, NTRK2, ERB4, FGFR1, MAP3K3, PRKDC) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Of note, BRAF or MAP3K8-fused cases may pursue a more aggressive course compared with tyrosine kinase–fused cases, especially in the presence of TERT promoter mutations.…”
mentioning
confidence: 99%
“…The diagnosis of Spitz tumors may be difficult on clinical, dermoscopic, and histologic grounds [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Clinically, they may present either as pigmented, hypopigmented, or non-pigmented lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation